Новые приключения Бабы Яги - Степанов Владимир Александрович (Лучшие стихи и сказки малышам, 2013)
Экземпляры: ДБ (20131217) / Инвентарный номер: 45383 / Цена: 62.00 / Сис.шифр: Д / Авт.знак: С 79 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6